Sosialisasi dan Pelatihan Framework Codeigniter Untuk Mahasiswa Universitas Muhammadiyah Jambi - Ikhsan, Muhammad; Helmina; Akbar, Zulfikri; Dani, Rian; Ediansa, Oka (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
With the various advantages that CodeIgniter has, there are still many who haven't used it because they don't know enough about the CodeIgniter framework. Just like at Muhammadiyah University of Jambi, students don't know about the CodeIgniter framework. Students' ignorance of the CodeIgniter framework is due to the lecturer's limitations in teaching, namely the lecturer's limited time to teach or limited time. So, lecturers at the Faculty of Science and Technology teach only material according to the established syllabus, they cannot teach material outside of that, such as: material about the CodeIgniter framework. Given this problem, the author intends to hold training for Muhammadiyah University Jambi students about web development and web creation with the CodeIgniter framework. With this training, students can learn about the history of the web, web development, the meaning of frameworks, the most important thing is that students can create their own web using the CodeIgniter framework.